Cardioprotective activity of fruits of Sechium edule - Neeraja, Kosanam; Debnath, Rabindra; Firdous, S. M. (Bangladesh Journal of Pharmacology, 2015)
The present work deals with the study of the ethanolic extract of fruits of Sechium edule for cardioprotective activity. Cardioprotective activity of the ethanolic extract of fruits of Sechium edule was determined by the administration of isoproterenol (60 mg/kg, s.c) for two days. Pretreatment with Sechium edule (200 mg/kg, p.o and 100 mg/kg, p.o) for 28 days in significantly (P<0.01) reduce the levels of serum SGOT, SGPT, ALP, LDH, CK, Total Cholesterol, triglycerides, LDL-C, VLDL-C and increase the levels of HDL-C. Histopathological studies of the hearts of ISO treated rats have showed infiltration of inflammatory cells and continuity in muscle fiber was lacking suggesting an irreversible cell injury. Animals treated with ethanolic extract of Sechium edule showed less degenerative changes compared to ISO - treated animals.